2020
DOI: 10.21203/rs.3.rs-23532/v1
|View full text |Cite|
Preprint
|
Sign up to set email alerts
|

WITHDRAWN: Physician factors associated with medical errors in Norwegian primary care emergency services. Based on a case – control study with patient complaints as an outset.

Abstract: Background Patient safety incidents are reported as relatively common. To unravel the reasons for these incidents in primary care emergency units (PCEU), patient complaints have been used as an outset. Methods We included the PCEUs in ten major cities and rural parts of Norway, covering one third of the population. In the initial part of our study a case-control design was used to evaluate factors related to complaints. The controls where a random sample of three physicians from the same PCEU and time-period a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…101 Some studies have shown the prevalence of MEs in Western countries; indeed, in this regard, a study in Norway showed that 53% of medical records were assessed as featuring errors. 102 Also, about 27% of patients reported at least 1 error during cancer follow-up in Denmark. 103 Moreover, MEs were involved in 26% and 74% of court verdicts in Spain and Massachusetts, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…101 Some studies have shown the prevalence of MEs in Western countries; indeed, in this regard, a study in Norway showed that 53% of medical records were assessed as featuring errors. 102 Also, about 27% of patients reported at least 1 error during cancer follow-up in Denmark. 103 Moreover, MEs were involved in 26% and 74% of court verdicts in Spain and Massachusetts, respectively.…”
Section: Discussionmentioning
confidence: 99%